2007
DOI: 10.1007/s00464-007-9326-5
|View full text |Cite
|
Sign up to set email alerts
|

Routine upper GI series after gastric bypass does not reliably identify anastomotic leaks or predict stricture formation

Abstract: Because the incidence of anastomotic complications and the sensitivity of upper GI series were both low, routine upper GI series did not reliably identify leaks or predict stricture formation. A selective approach, whereby imaging is reserved for patients with clinical evidence of a leak or stricture, may be more appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 29 publications
0
27
1
5
Order By: Relevance
“…Most conclude that routine Gastrografin swallow studies on POD 1 are not useful or costeffective methods of early detection of anasto motic leaks. 17,[29][30][31][32][33][34] However, 2 studies published on LRYGB have conducted sensitivity analyses comparing sensi tivies of clinical signs verus routine Gastrografin swallows. These 2 studies found clinical signs to be less sensitive and there fore support the use of routine contrast studies.…”
Section: Discussionmentioning
confidence: 99%
“…Most conclude that routine Gastrografin swallow studies on POD 1 are not useful or costeffective methods of early detection of anasto motic leaks. 17,[29][30][31][32][33][34] However, 2 studies published on LRYGB have conducted sensitivity analyses comparing sensi tivies of clinical signs verus routine Gastrografin swallows. These 2 studies found clinical signs to be less sensitive and there fore support the use of routine contrast studies.…”
Section: Discussionmentioning
confidence: 99%
“…8 The patient was given only clear liquids on the first operative day and then was advanced to a full liquid diet on the second postoperative day. Patients were seen postoperatively at 2 weeks, every 3 months for the first year, and annually thereafter.…”
Section: Postoperative Carementioning
confidence: 99%
“…Pierredon-Foulongne et al [7] concurred that imaging was key in assessing complications, both early and late. However, as surgeons performing LRYGB have begun publishing data to support exclusion of routine postoperative UGI for this more complicated procedure, it calls into question whether it is necessary after the less complex LAGB [7,[9][10][11]. Indeed, one recently published study by Frezza et al [8] sought to verify that UGI is not routinely necessary based on no leaks and no interventions after 97 banding studies.…”
Section: Introductionmentioning
confidence: 96%